(untitled) (Fiep Bulletin - online, 2012)
The article focuses on the effect of the slogan ’education through sport’ on the pedagogical work in schoolphysical education, and briefs some aspects regarding the pedagogical potentials of youth sport organized in clubs.The author also approaches the difficulties faced by PE in order to be justified as an obligatory school subject,discusses justifications strategies, presents the cul-de-sac of the ’education through sport’ motto, and offers a briefoutline of a constructive alternative based on the Gordijn’s relational view of movement and its didacticalelaboration. Finally, the author gives an idea of quality Physical Education by presenting a number of characteristictraits, such as the longitudinal planning and the constructivist didactics, and states that providing quality PE willcertainly assure the survival of this discipline as an important aspect of the school curriculum.